THE INFLUENCE OF USING NHT TECHNIQUE TOWARD STUDENTS’ READING COMPREHENSION AT THE TENTH GRADE OF SMA NEGERI 1 BATANGHARI ACADEMIC YEAR 2014/2015 - Syaifudin Latif Darmawan (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2015)
Abstract: The objective of the research is to know whether there is influence of using Number Head Together technique toward students’ reading comprehension. The subjects of thisresearch are two classes consist of 26 students of class X1 as experimental group and 27 students of class X2 as control group. The design of this research is quasi experimental design. In collecting the data, the researchers use a test. The test consits of pre-test and post-test. To analyze data, the researcher uses ttestformula. The result of the research shows that tcount =3,81 and tdaf 2,70 (on criteria 1) and tdaf =2,02 (on criteria 2). So, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. It means that there is influence of using Number Head Together technique toward students’ reading comprehension at the tenth grade of SMA N 1 Batanghari Academic Year 2014/2015.Key words: Number Head Together Technique, Reading Comprehension.